Antagonists with negative intrinsic activity at delta opioid receptors coupled to GTP-binding proteins. - Costa, T (1989)
According to classical models of drug-receptor interactions, competitive antagonists share with agonists the ability to bind to a common site on the receptor molecule. However, they are different from agonists, as they cannot trigger the "stimulus" that leads to biological responses--i.e., they lack intrinsic activity. For those receptors whose signals are transduced to effector systems by GTP-binding regulatory proteins (G proteins), a mechanistic equivalent of such a stimulus is an increased ability of agonist-bound receptor to accelerate nucleotide exchange and thus GTPase activity on the G-protein molecule. Here we show that for a member of this family of receptors (delta opioid receptors in membranes of NG108-15 neuroblastoma-glioma cells), two types of competitive antagonists can be distinguished. One type has no intrinsic activity, since it neither stimulates nor inhibits the GTPase activity of G proteins and its apparent affinity for the receptor is not altered by pertussis toxin-mediated uncoupling of receptor and G protein. The second type, however, can inhibit GTPase and thus exhibits negative intrinsic activity; its affinity for receptors is increased following uncoupling from G proteins. The existence of antagonists with negative intrinsic activity may be a general feature of several classes of neurotransmitters or hormone receptors and calls for a reevaluation of biological effects produced by competitive antagonists.